2020
DOI: 10.1111/codi.15408
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of faecal immunochemical testing for 2‐week‐wait colorectal patients during the COVID‐19 pandemic: an observational cohort study reporting a new service at a regional centre

Abstract: Aim:The COVID-19 pandemic has resulted in the near-complete loss of routine endoscopy services. We describe a major reorganization of service at a regional referral centre (Royal Surrey NHS Foundation Trust) to manage the crisis. Faecal immunochemical testing (FIT) was implemented for triage to make optimum use of limited diagnostic resources. Consultations were switched from face-to-face to telephone. Our aim was to evaluate the impact FIT had on resource allocation and patient diagnoses in the first 3 months… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 21 publications
0
24
0
Order By: Relevance
“…94% of samples were returned, of which 34% were interpreted and positive and were followed by colonoscopy. The CRC diagnosis rate with this pathway was 3.7% (14 CRC of 122 colonoscopies), comparable to the pre-COVID detection rate of 3.9% [31]. Miller et al triaged referred patients to alternate testing modalities of FIT with CT scan, FIT only, direct colonoscopy or clinical follow up.…”
Section: Triage and Alternate Screening Pathwaysmentioning
confidence: 84%
“…94% of samples were returned, of which 34% were interpreted and positive and were followed by colonoscopy. The CRC diagnosis rate with this pathway was 3.7% (14 CRC of 122 colonoscopies), comparable to the pre-COVID detection rate of 3.9% [31]. Miller et al triaged referred patients to alternate testing modalities of FIT with CT scan, FIT only, direct colonoscopy or clinical follow up.…”
Section: Triage and Alternate Screening Pathwaysmentioning
confidence: 84%
“…With the COVID‐19 pandemic reducing access to endoscopy, FIT was recommended for triage by NHS England for those within the higher risk groups [26]. The RSFT demonstrated that using FIT enabled safety‐netting with a watch and wait approach, but also reduced overall colonoscopy from 62% to 34% of TWW patients [27].…”
Section: Discussionmentioning
confidence: 99%
“…Maclean et al demonstrated FIT results could be obtained in over 94% of referrals by sending the kit directly to patients and, using a 10 μgHb/g cut-off, a half of the patients were excluded from further investigations. 16 If this were applied in our cohort, 35.7% of the patients with an FIT result would have been excluded. We believe FIT testing should be considered imperative for all 2ww referrals without a mass or rectal bleeding, and we recognise this was recommended by a recent independent review of diagnostic services for NHS England.…”
Section: Discussionmentioning
confidence: 99%